Flow visualization around panel shapes of soccer ball - Hong, S.; Asai, T.; Seo, K. (Procedia Engineering, 2015)
In recent study, trajectory analysis and wind tunnel experiments were used to glean information for comparing the non-spin aerodynamics of various soccer balls. However, there has been no study on the flow of air around soccer balls with respect to the shape, number, and orientation of their panels. The subject of our experiment was a soccer ball known as Cafusa and the air flow on the surface of the ball was examined using PIV. The Cafusa is characterized by the shapes of the panels changing significantly depending on the orientation of the ball, so our experiment with the Cafusa was performed in order to examine the effects of the panels. Therefore, the present study has focused its investigation on the flow visualizations applied to a soccer ball through its three faces by 2D-PIV. The results showed the separation point changes depending on the number of seams. Moreover, even with a panel orientation that has the same number of seams, the separation point can change depending on the panel intervals and the lift force.